IN VITRO TUBERIZATION AND QUANTITATIVE ANALYSIS OF COLCHICINE USING HPTLC IN GLORIOSA SUPERBA. L AN ENDANGERED MEDICINAL PLANT OF - AMZAD BASHA KOLAR; M. GHOUSE BASHA (International Journal of Pharma and Bio Sciences, 2014)
Gloriosa superba. L has been a source of medicine right from ancient times. The tubers of this plant are sold in Indian herbal market as an important source of an alkaloid colchicine. Surface sterilized seeds of Gloriosa superba were soaked overnight in 1% GA3 on the next day seeds were planted on germinating media containing MS basal salts with 0.5 mg/l GA3 and 1.0 mg/l BA, 1% sucrose and 0.8% agar. 72.5% of seed germination was observed. The germinated seeds were transplanted on MS basal medium supplemented with 1.0 mg/l BAP, 0.05 mg/l GA3, 9.5 mg/l NAA and 6% sucrose which led to 90% tuber induction within 6 weeks of culture. Since there is a great demand of colchicine in the market, we have made an attempt to estimate the colchicine content in different parts of the plant like leaf, seed, pericarp, tuber and in vitro produced tuber using High Performance Thin Layer Chromatography, using a mixture of Ethyl acetate:Methanol (10:1.3 v/v) as mobile phase and precoated silica gel F254 TLC aluminium sheets as the stationary phase. The detection of spot was carried out at 350nm. The calibration curve was found to be linear between 100 to 600 ng/spot for colchicines. The results revealed that in vitro tuber had highest amount (0.14249%) of cochicine, followed by in vivo seed (0.10900%), tuber (0.05761%), leaves (0.46470%) and pericarp (0.04574%). The proposed method can be used to determine the colchicine content in Gloriosa superba.